I SEMINÁRIO NACIONAL DE EDUCAÇÃO EM CIÊNCIAS SOCIAIS: Notas informativas - Souza, Adriana Aparecida de; Gomes, Ana Laudelina Ferreira; Lima, José Gllauco Smith Avelino de; Fortes, Lore (Revista Inter-Legere, 2013)
I SEMINÁRIO NACIONAL DE EDUCAÇÃO EM CIÊNCIAS SOCIAIS: Notas informativas